Method to form semiconductor quantum dot (QD) thin films by igniting a flame at air-liquid interface: CdS and WO3 - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Colloid and Interface Science, 2015)
We reveal an easy, inexpensive, efficient one step flame synthesis of semiconductor/metal oxide thin films at air-liquid interface, subsequently, transferred on suitable substrate. The method has been illustrated by the formation of CdS and Wo(3) QDs thin films. The features of the present method are (1) Growth of thin films consisting of 0.5-2.0 nm sized Quantum Dots (QDs)/(ultra-small nanoparticles) in a short time, at the air-liquid interface which can be suitably transferred by a well-known Blodgett technique to an appropriate substrate, (2) The method is suitable to apply layer by layer (LbL) technique to increase the film thickness as well as forming various compositions as revealed by AFM measurements. The films are characterized for their structure (SAED), morphology (TEM), optical properties (UV-Vis.) and photoluminescence (PL). Possible mechanism of formation of QDs thin film and effect of capping in case of COS QDs is discussed. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: CdS; Flame synthesis; interface; Quantum Dots (QDs); thin film; WO3